Draft Five Year Plan 1978-83 and Annual Plan 1979-80 (Vol. III - Sectoral Reviews) Uttar Pradesh Planning Department - Planning Commission (Planning Commission, 1979)
General Economy—Even after two decades of planning, the economy of the State remains predominantly agricultural. Eighty-five per cent of the population (estimated to be 99 millions in 1977) is dependent on agriculture and 75 per cent of the total working force is engaged in agricultural pursuits. Naturally the State remains backward with low per capita income and inadequate savings for investment resulting in lack of industrialization. The first two plans (1951—60) of the State gave emphasis on agriculture, irrigation and social services, Industrial development on a planned basis was initiated only during Third Plan period.
Sectoral Reviews
Government of Uttar Pradesh